Job Satisfaction of MSME Employees: Maslow's Perspective - Pratama, Okky Yudha; Muslih, Basthoumi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research objectives: This study aims to analyze the impact of salary and incentives on the level of job satisfaction of employees of Sumengko shuttlecock MSMEs, Nganjuk. Design/Method/Approach: This study applies a quantitative method with a causality approach. The research location is in Shuttlecock MSMEs in Sumengko Village, Sukomoro District, Nganjuk Regency. Data collection was carried out through a questionnaire with a total sampling technique, involving the entire research population consisting of 62 employees in 5 shuttlecock manufacturers. The data were analyzed using multiple linear regression with the help of SPSS statistical software. Research Findings: Based on the results of multiple linear regression analysis, the variables Salary (X1) and Incentive (X2) partially have a positive and significant influence on Employee Job Satisfaction (Y). In addition, simultaneous tests show that together, these two variables also contribute positively and significantly to Employee Job Satisfaction (Y). Theoretical contribution/originality: this study enriches the literature on employee job satisfaction, especially in MSMEs in the shuttlecock sector, which is rarely studied. This study offers a maslow perspective on compensation management. Practice / Policy Implications: Incentives in Sumengko Shuttlecock MSMEs in Nganjuk Regency need to be increased because the incentive variable only affects 0.160 equivalent to 16% on employee job satisfaction. Research limitations: This study shows that salary and incentive variables contribute 80.1% to employee job satisfaction. The rest, namely 19.9%, is influenced by other factors that have not been analyzed in this study and require more in-depth study.